2017
DOI: 10.1139/cjas-2016-0230
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of meat quality traits and the proteome profile between low pH and high pH muscles in longissimus dorsi of Berkshire

Abstract: This study was conducted to assess the molecular mechanism of meat quality between low-and high-pH muscles using two-dimensional gel electrophoresis (2DE) with matrix-assisted laser desorption ionization timeof-flight mass spectrometry (MALDI-TOF/MS) on longissimus dorsi muscles from Berkshire species, assigned to high-(5.92 ± 0.02) and low-pH groups (5.55 ± 0.03). The high-pH group had a lower lightness, yellowness, drip loss, shear force, and a higher National Pork Producers Council color than the low-pH gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…ß enolase is the muscle-specific isoform of enolase, catalyzing the hydrolysis of 2phosphoglycerate to phosphoenolpyruvate. A previous study has identified greater amounts of ß enolase in early PM pork LD samples with lower 24 hr PM pH (pH 5.55 + 0.03) and lower WHC (Subramaniyan et al, 2017). These findings are in contradiction to the current results that showed more abundance of ß enolase in the NpH group (Figure 3.3).…”
Section: Additional Abundant Soluble Proteinscontrasting
confidence: 99%
“…ß enolase is the muscle-specific isoform of enolase, catalyzing the hydrolysis of 2phosphoglycerate to phosphoenolpyruvate. A previous study has identified greater amounts of ß enolase in early PM pork LD samples with lower 24 hr PM pH (pH 5.55 + 0.03) and lower WHC (Subramaniyan et al, 2017). These findings are in contradiction to the current results that showed more abundance of ß enolase in the NpH group (Figure 3.3).…”
Section: Additional Abundant Soluble Proteinscontrasting
confidence: 99%
“…It protects the cell against reactive oxygen species. Other studies have identified a relationship between peroxiredoxin and meat quality or color traits in beef [ 84 , 85 , 86 , 87 ] and chevon [ 88 ]. Activation of the AP-1 transcription factor induces the expression of many antioxidants, including peroxiredoxin and glutathione reductase [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…The longissimus dorsi (LD) of Berkshire pigs was classified into high-pH (HpH; 5.92 ± 0.02; n = 10) or low pH (LpH; 5.55 ± 0.03; n = 10) groups based on 24 h postmortem pH. The abundance of Prdx6 was greater at 0 h postmortem in the HpH compared with the LpH group (Subramaniyan et al, 2017). When LL chops were categorized as normal pH (NpH; 5.59 ± 0.01; n = 10) and LpH (5.42 ± 0.01; n = 10) based on 14 d postmortem pH, Zuber et al (2021) reported a greater abundance of Prdx2 at 45 min postmortem in NpH compared with LpH groups.…”
Section: Postmortem Phmentioning
confidence: 99%